TRAINING AND PRACTICE OF CARVING AT LAUTECH ART SCHOOL: TRAINEES’ FEEDBACK - Olatunbosun, Odeniyi Akinkunmi (Srawung: Journal of Social Sciences and Humanities, 2025)
Carving is a subtractive sculpture technique. In Nigeria, it evolved from traditional to contemporary art periods with its training domiciled in informal and formal art schools. Existing literature largely addressed traditional, informal training methods and historical practices of carving, however, there is a notable lack of focused studies on carving training and practice in formal Nigerian Art schools. This study investigates the training and practice of carving at LAUTECH Art School via students’ and alumni feedback. It aims to document existing Carvings, assess the pedagogical approaches employed in carving training, identify challenges limiting effective carving training and practice, and propose potential reforms to revitalize and sustain the carving practice in formal Nigerian art schools. The study adopts a qualitative research methodology, collecting primary data through surveys, semi-structured interviews, questionnaires, and field investigation. Secondary data were sourced from academic journal articles, and reports on carving practice in Nigeria. All data gathered were subjected to qualitative analysis. Findings revealed that carving is not a preferred sculpture technique at LAUTECH Art School. The lack of infrastructure dedicated to carving and insufficient staffing hinder effective training. Respondents’ concern about carving’s economic viability resulted in a declining student interest in the practice. The study recommends increased investment in tools and materials, recruitment of specialized instructors, integration of traditional and modern carving methods, and the organization of regular exhibitions and training programs. These efforts could revitalize interest in carving, enabling LAUTECH Art School to preserve and promote Nigeria’s rich carving heritage.